If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + -4 = 7x + 2 + -1x Reorder the terms: 2(-3 + x) + -4 = 7x + 2 + -1x (-3 * 2 + x * 2) + -4 = 7x + 2 + -1x (-6 + 2x) + -4 = 7x + 2 + -1x Reorder the terms: -6 + -4 + 2x = 7x + 2 + -1x Combine like terms: -6 + -4 = -10 -10 + 2x = 7x + 2 + -1x Reorder the terms: -10 + 2x = 2 + 7x + -1x Combine like terms: 7x + -1x = 6x -10 + 2x = 2 + 6x Solving -10 + 2x = 2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -10 + 2x + -6x = 2 + 6x + -6x Combine like terms: 2x + -6x = -4x -10 + -4x = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 -10 + -4x = 2 + 0 -10 + -4x = 2 Add '10' to each side of the equation. -10 + 10 + -4x = 2 + 10 Combine like terms: -10 + 10 = 0 0 + -4x = 2 + 10 -4x = 2 + 10 Combine like terms: 2 + 10 = 12 -4x = 12 Divide each side by '-4'. x = -3 Simplifying x = -3
| 3y+4=5-y | | (X-3)(3-y)=0 | | .5x+.375x+x= | | 24*2x*x=72000 | | -2n-2=-2n-7 | | 12k=8 | | 3.4(x+3)=15.3 | | 12(x)=5(y) | | z^2-(1+2i)z+1+7i=0 | | 6(4-x)+6x=244 | | 299,792,000/x=0.50 | | 0.5x+2x=7 | | 7-6x=x-49 | | .5(3x-24)=9 | | 6x-(2x+7)=3+4(x-9) | | 2x+1=3+4x | | m^2+16m=-49 | | -8m-10+6m=36 | | 5x^2+18x+45=0 | | 5x+9=15-6 | | 1+8y=-32 | | X^2-4x-12y+16=0 | | 8+6x+3x=-10 | | 3k-15=78 | | 8(5n-4)+8=-264 | | 6c-64=80 | | Y/3-15=-6 | | -7m-5=37 | | 4m+70=-30 | | 8y+4(7+y)=3(y-2)+10 | | p(t)=(348)3t/4 | | 4+7x-5x=-6 |